1999
DOI: 10.1021/jp993927y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Infrared Spectroscopy of Vibrational States Prepared by Photoinduced Electron Transfer in (CN)5FeCNRu(NH3)5-

Abstract: The picosecond time-resolved infrared spectra of (CN)5FeCNRu(NH3)5 - were collected following optical excitation and reverse electron transfer. The measured reverse electron transfer rates are greater than 3 × 1012 s-1. In both formamide and deuterated water solutions, vibrational excitation in CN stretch modes is found after reverse electron transfer. The transient spectra at both earlier (1−35 ps) and later (10 ns) times give evidence of environment−solute coupling that can be accounted for by solvent heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 61 publications
3
46
0
Order By: Relevance
“…Previous work has assigned the electronic transition in FeRu to be a MMCT excitation from the Fe II to the Ru III , resulting in Fe III and Ru II . 22 As shown in Fig. 1d (Fig.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Previous work has assigned the electronic transition in FeRu to be a MMCT excitation from the Fe II to the Ru III , resulting in Fe III and Ru II . 22 As shown in Fig. 1d (Fig.…”
mentioning
confidence: 58%
“…[17][18][19][20][21][22][23][24][25] Transient IR, optical, and resonance Raman studies of FeRu in polar solvents have suggested the 7 involvement of some of the high frequency ν CN vibrations in the charge transfer process 19,23 and significant excitation in the ν CN modes upon ultrafast back electron transfer. 22 We have extensively studied the vibrational anharmonic couplings among ν CN modes and the role of solvent in modulating the molecular structure, anharmonic couplings, and the oxidation states of the metals in the FeRu complex. [26][27] This work introduces 2D VE spectroscopy to connect the complementary electronic and vibrational spectroscopic signatures collected previously in FeRu.…”
mentioning
confidence: 99%
“…28 In an analogous system where one of the Ru atoms is replaced with Fe, the bridging and terminal CN stretching modes showed relaxation times on the order of picoseconds in D 2 O using 200 fs pulses. 29 It is possible, however, that significant portion of the vibrational relaxation occurs also on a similar time scale as solvation RuRu in water, and that this component of vibrational relaxation was not too fast to be resolved by the published infrared spectroscopy experiments (which had a resolution of several hundred femtosecond or longer). It is also possible is that the vibrational excess energy is distributed to FranckCondon inactive modes and is not observed spectroscopically.…”
Section: Resultsmentioning
confidence: 99%
“…Transient IR studies of the FeRu molecule and its analogues find a high degree of vibrational excitation in the ν CN modes upon ultrafast back electron transfer (BET). 14,15,18 The role of the ν CN modes in the metal-to-metal charge transfer (MMCT) excitation, and subsequent BET, of FePtFe dissolved in D 2 O has also been recently studied using various nonlinear spectroscopies. 20,21,26 These studies have found >6 quanta of vibrational energy deposited into the ν b mode following BET and provided experimental evidence that ν CN modes are both coherently and incoherently coupled to the charge transfer reaction.…”
Section: Introductionmentioning
confidence: 99%